The Meaning of the Integrity Zone in the Prosecutor's Office: A Study of Legal Hermeneutics - Setia Untung Arimuladi; Yos Johan Utama; Teddy Asmara (Yuridika, 2022)
Integrity Zone is proposed to improve the quality of public services, and as an effort to realize clean and good government, even it is still hard to fully realize in specific law enforcement agencies, such as the Prosecutor's Office of the Republic of Indonesia. For that purpose, the implementation of the related law should be accompanied by an understanding that humans are the prominent entities in realizing the norms contained in the integrity zone. The potential for abuse of duties and authority by individual prosecutors that can at least be categorized as illegal acts should be appropriately addressed. A qualitative approach with the hermeneutic method was employed in this study to explore and examine the legal meanings behind the phenomena in the integrity zone through correct interpretation. It is concluded that there is a limitation in regulating the integrity zone within the attorney's office and not referring to the correct interpretation of the correlated law. The legal hermeneutic perspective in building an integrity zone at the Prosecutor's Office must be built based on a culture of zero tolerance for any illegal act, which refers to planting and strengthening the roots of human conscience within the Prosecutor's Office.